Reaction delay time in the process of detection and discrimination of acoustic signals - Andrzej RAKOWSKI; Antoni JAROSZEWSKI (Archives of Acoustics)
Reaction delay times in listeners with musical training to auditory stimuli at a level near the threshold of hearing were determined. Listeners were to detect these stimuli (detection) or state whether successive stimuli have the same or different pitch (discrimination). Reaction times in listeners in discrimination were distinctly longer than in detection tasks. Reaction delay time provide information about the relative difficulty of the task.